MANFAAT TANAMAN TERATAI (Nymphaea sp., Nymphaeaceae) di DESA ADAT SUMAMPAN, KECAMATAN SUKAWATI, KABUPATEN GIANYAR, BALI - Budiwati, Gusti Ayu Nyoman; Kriswiyanti, Eniek (SIMBIOSIS; Vol 2 No 1 (2014), 2014)
his purpose of this research was to determine the benefits of the lotus plant in Sumampan Village, District of Sukawati, Gianyar, Bali. The research was conducted from 4 to 16 February 2013. The method was used in this study is exploratory survey by direct observation and interviews with one main informant and 15 KK from 3 banjar. The results showed there were 11 kinds of lotus : lotus sudamala ( Nymphoides indica ) (4.54 %), yellow lotus (21.21 %), dark blue lotus ( Nymphaea stellata Wild ) (12.12 %), pink lotus (16.66 % ), violet lotus (9.09 %), purple lotus (9.09 %), white lotus (Nymphaea nouchali Burm f.) (18.18 %), light blue lotus (Nymphaea stellata Wild ) (3.03 %), lotus tutur (1.51 %), lotus dedari (1.51 %) and lotus brumbun (3.03 %). The lotus plant is used as a upakara / banten 77.41 % , 16.12 % as ornamental plants, while 6.45 % as a medicine for breast cancer drug, arthritis, headaches, stress, fear, and cleanser the liver and pancreas. As a medicine, lotus plant was used in it’s from as tempel, solutions, pupuk and boreh. Key word: exploratory survey, benefits lotus, tempel, pupuk, boreh